ВЕРБАЛІЗАЦІЯ КОНЦЕПТУ КОХАННЯ В РОМАНІ АХІЛЛА ТАТІЯ „ЛЕВКІППА І КЛІТОФОНТ” - Chakal (Makar), Inesa; Оліщук, Роксоляна Леонідівна (Видавничий дім Дмитра Бураго, 2016)
This article is an attempt to determine the concept of LOVE in a novel “Leucippe and Clitophon”, written by the ancient Greek writer Achilles Tatius, as a verbalized concept of human consciousness. The findings of present investigation show that the number of noun, verbal, adjectival tokens verbalizes the concept of LOVE and sometimes expands their vocabulary meaning, creating new connotations. The results prove that the list of narrative techniques is an important instrument for analysing this research issue. У статті зроблена спроба дослідити концепт КОХАННЯ в романі давньогрецького письменника Ахілла Татія “Левкіппа і Клітофонт” як складне за структурою і змістом вербалізоване поняття людської свідомості. Виявлено, що концепт КОХАННЯ вербалізується низкою іменникових, дієслівних і прикметникових лексем, які подекуди розширюють своє словникове значення, набуваючи нових конотативних значень. Встановлено, що активним інструментом розгортання досліджуваного концепту є художні засоби.
Verbalization of the Concept LOVE in the Novel of Achilles Tatius “Leucippe and Clitophon”
Keywords: концепт; вербалізатор; художні засоби; давньогрецький роман; Ахілл Татій; Achilles Tatius; concept